HER2 alterations in non-small cell lung cancer (NSCLC): from biology and testing to advances in treatment modalities - Ismail, Ahmed; Desai, Aakash; Boumber, Yanis (Frontiers in Oncology, 2025)
Lung cancer remains the leading cause of cancer-related deaths worldwide. Non-small cell lung cancer (NSCLC), which accounts for approximately 85% of all lung cancers, is a biologically diverse disease characterized by a wide range of molecular alterations. Among these, HER2 (human epidermal growth factor receptor 2, or Erb-B2 Receptor Tyrosine Kinase 2 (ERBB2)), a gene more commonly associated with breast cancer, has emerged as an important oncogenic driver in NSCLC, particularly within the adenocarcinoma subtype. HER2 alterations are notably more prevalent among non-smokers, with estimates suggesting that up to 50–80% of patients with HER2 mutations or amplifications have no smoking history. In our comprehensive review, we outline the molecular biology of HER2 in NSCLC, including distinctions between HER2 mutations, amplification, and overexpression, and we delve into the diverse diagnostic complexities. We also review NCCN guidelines and the performance of newer FDA-approved testing assays (such as Guardant360 and FoundationOne) in detecting HER2 alterations and circulating tumor DNA (ctDNA) as a tool for treatment response monitoring. Furthermore, we present updated clinical trial data for published HER2-targeted agents and explore ongoing clinical trials examining combinatorial therapies and next-generation HER2-targeted agents such as zongertinib, A166, ARX788, SHRA1811, and others. Given the rapid evolution in this field, our review offers a timely and comprehensive synthesis of the current state and future directions for HER2-altered NSCLC.